Analysis of multi peril crop insurance loss ratiosAnalysis of multi peril crop insurance loss ratios - Žalgirytė, Lina; Račkauskas, Gediminas (Lietuvos matematikos rinkinys, 2010)
In the first part of this paper, the distribution of loss ratios for five crops was analyzed. The results show that the truncated shifted Pareto distribution can be used for crop insurance loss ratios approximation. In the second part, the relationship between weather conditions and crop insurance loss ratios was tested. Results suggest that this dependency is weak. It shows that crop insurance loss ratios are affected not only by weather conditions – monthly growing degree days and monthly precipitation – but also by other factors.
Keywords: multi peril crop insurance; loss ratio; truncated shifted Pareto distribution; multiple linear regression